HEALTH BELIEF MODEL DALAM KEARIFAN LOKAL PEMANFAATAN TUMBUHAN OBAT DI KABUPATEN MANGGARAI BARAT - Duryatmo, Sardi; Sarwoprasojo, Sarwititi; Lubis, Djuara P; Suharjito, Didik (Media Bahasa, Sastra, dan Budaya Wahana, 2024)
The tradition of using medicinal plants in Waesano Village, Sanonggoang District, West Manggarai Regency, East Nusa Tenggara Province, is still maintained to this day. They use various plants that grow wild in the 4,000-hectare Sesok forest to maintain their health. The nature of their treatment is preventive and curative. This research uses a qualitative method. Data analysis was carried out by applying the individual health belief model or healtf belief model in determining attitudes to do or not to perform health behaviors (Conner 2005). The model was developed by Rosenstock in 1950 to study and promote improved health care. The model consists of six constructs, namely perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and motivation related to individual motivation to always live a healthy life. The results of the study produced findings that a person's susceptibility to certain diseases encourages them to consume certain medicinal plants. Perceived susceptibility or vulnerability is defined as whether a person has a high risk of a disease. Perceived severity talks about an individual's beliefs about the seriousness or severity of a disease. Information regarding the severity of a disease comes from medical or physician and knowledge. Perceived benefits are related to a person's view of the value or usefulness of the new healthy behavior that they will do. People tend to adopt healthier behaviors when they believe that new behaviors can inhibit the progression of the disease. Regarding perceived benefits, the residents of Waesano Village until now continue to use a variety of medicinal plants to maintain their health because they have obtained many benefits or uses. This behavior is partly because the consumption of medicinal plants has been proven to be efficacious in overcoming many health problems that they experience. Many residents have proven the efficacy of medicinal plants based on empirical experience to overcome various diseases.Keywords: health belief model, local wisdom, health behavior